DINAMIKA SOSIAL EKONOMI PETANI GAMBIR KAULAK DI KENAGARIAN MAEK KECAMATAN BUKIT BARISAN KABUPATEN 50 KOTA (2005-2013) - Ansofino, Ansofino; Hardi, Etmi (Pendidikan Sejarah, 2014)
The aim of this thesis, first: to describe the background of gambir kaulak farmers in kenagarian Maek , second: Describing the social and economic life of gambir kaulak farmers at kenagarian Maek, sub-district Bukit Barisan, District 50 KotaÂ ( 2005-2013 ) . This study uses historical research. The type of data used is primary data and secondary data.The results showed that, first: activities of gambir kaulak farmers which carried by society in Nagari Maek are done in groups on several locations which the agricultural site conditions are not the same from one location to another . Gambir kaulak farmers activities is utilization of earnings for the purpose of improving Nagari Maek villagers incomes outside the other kind of agriculture, canÂ improve Nagari economic conditions, also improving the welfare of the community . Second, by the presence of kaulak activity , socio-economic conditions of society is increasing. From the economic point of view they have been able to meet the needs and buying luxury goods , turning community Maek to consumptive lifestyle, able to send their children to university . Then in terms of social, creating a new color in the community of Nagari Maek .From the research that has been carried out it can be concluded that, the gambir farmers activities which carried by societyÂ have been able to sustain community economic, but not evenly .